An Analysis of Gottlieb’s Subtitling Strategies: Comparing the Official and Non-Official Subtitles of Zootopia Movie - Haris Chaerul Fikri (Passage, 2017)
The study is aimed to compare the official and non-official Indonesian subtitles that are used in Zootopia movie as well as to analyze, investigate, and elaborate the strategies employed by the official and non-official subtitles. Employing a qualitative approach and comparative method, this study uses Gottlieb’s (1992) ten subtitling strategies to find the similarities and differences in the official and non-official Indonesian subtitles. In term of similarities, the result shows that there are 511 utterances that are translated by using similar strategies and 531 utterances using different strategies. The differences can be found when the utterances contain a word that refers to an object, cultural words, proper names, and insult words. Additionally, the differences also occur in the degree of formality, careful use of punctuation, precision of translation, and subjectivity of the translation.Keywords: Audiovisual Translation (AVT), Subtitle and Subtitling, Subtitling Strategies